Photoprotective efficacy and physicochemical stability of sunscreen gel containing Averrhoa bilimbi L. leaf extract - Wittami, Rega Gustiya; Rahayyu, Annisa Maulidia; Ramadhani, Untia Kartika Sari (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2025)
Chronic UV-B exposure causes significant skin damage, necessitating effective photoprotective strategies. This study developed and evaluated sunscreen gel formulations containing ethanolic extracts of Averrhoa bilimbi leaves at varying concentrations. Extraction was performed using ultrasonic-assisted extraction (UAE), while sun protection factor (SPF) determination employed the Mansur spectrophotometric method. Four gel formulations were prepared: F0 (0%, control), F1 (0.2%), F2 (1%), and F3 (5% extract). Physicochemical characterization revealed that all formulations exhibited acceptable organoleptic properties, homogeneity, pH (4.5 to 7.0), viscosity (2,000 to 50,000 cps), spreadability (5 to 7 cm), and adhesiveness (>1 second). Accelerated stability testing demonstrated stable pH, viscosity, spreadability, and SPF values, although adhesiveness showed statistical variation while remaining within acceptable limits. SPF analysis revealed concentration-dependent photoprotective efficacy: F1 achieved maximum protection, while F2 and F3 demonstrated ultra protection, with F3 exhibiting the highest SPF value of 36.9. These findings confirm that increased A. bilimbi extract concentration correlates with enhanced photoprotective activity, establishing the potential of this natural ingredient for sunscreen applications.